The subject matter of arbitral tribunals in the resolutions of the Permanent Council (1776–1788) - Głuszak, Marcin (Czasopismo Prawno-Historyczne, 2021)
Original version: Problematyka sądownictwa polubownego w rezolucjach Rady Nieustającej (1776–1788), “Czasopismo Prawno-Historyczne” [Journal of Legal and Historical Sciences], 2016, vol. 68, issue 2, pp. 85–108.